Model za učinkovito upravljanje podatkov iz uporabe - primer proizvodnje izdelkov bele tehnike - Meža, Peter (Strojniški vestnik, 2005)
A company that wants to stay competitive has to keep up to date with the quality of products on the market, and constantly has to remove all the defects from its critical products. For this reason companies, depending on their size and type of activity, need a specific data-information integration model for the exploitation phase. Structured exploitation data increases the level of work quality and incorporates experience from former lines of products in the process of development or improving current products. For the needs of management quality the recurrent feedback loop was supplemented with the engineer model of service order, which includes an inventory of defect mechanisms. The information flow between fieldwork repairers and the company is illustrated in the case of a production company. The specification of the data model, which is based on defect presentation, presents the knowledge of defect mechanisms and causes. We used the model of the codification of defects. It covers the total area of states and causes in the structured form,which enables the company to easily acquire data as well as organized knowledge on the basis of typified defects that occur in the product lifecycle. Product-repair data available in one place enables a direct data transformation back to the feedback loop of the company. The model presented in this paper offers support to the TQM methods as well as the basis for carrying out correction measures in the production company. The structured data in the service-order model make it possible to navigate in the product-failure net.
Keywords: kakovost izdelkov; zanesljivost; garancije; analize podatkov; tehnični servisi; zagotavljanje kvalitete; kvaliteta; management; upravljanje; baze podatkov; servisiranje